Does pain sensitivity change by migraine phase? A blinded longitudinal study. (December 2017) - Uglem, Martin; Omland, Petter Moe; Nilsen, Kristian Bernhard; Tronvik, Erling; Stovner, Lars Jacob; Hagen, Knut; Linde, Mattias; Sand, Trond
Objective: Studies suggest that pain thresholds may be altered before and during migraine headaches, but it is still debated if a central or peripheral dysfunction is responsible for the onset of pain in migraine. The present blinded longitudinal study explores alterations in thermal pain thresholds and suprathreshold heat pain scores before, during, and after headache. Methods: We measured pain thresholds to cold and heat, and pain scores to 30 seconds of suprathreshold heat four times in 49 migraineurs and once in 31 controls. Sessions in migraineurs were categorized by migraine diaries as interictal, preictal (≤one day before attack), ictal or postictal (≤one day after attack). Results: Trigeminal cold pain thresholds were decreased ( p = 0.014) and pain scores increased ( p = 0.031) in the ictal compared to the interictal phase. Initial pain scores were decreased ( p < 0.029), and the temporal profile showed less adaptation ( p < 0.020) in the preictal compared to the interictal phase. Hand cold pain thresholds were decreased in interictal migraineurs compared to controls ( p < 0.019). Conclusion: Preictal heat hypoalgesia and reduced adaptation was followed by ictal trigeminal cold suballodynia and heat hyperalgesia. Our results support that cyclic alterations of pain perception occur late in the prodromal phase before headache. Further longitudinal investigation of how pain physiology changes within the migraine cycle is important to gain a more complete understanding of the pathogenic mechanisms behind the migraine attack.